Dodaj sumy algebraiczne i oblicz ich wartość liczbową dla a=2 ; b= -3

a) (a+b)- (5-b) + (a-4) =
b) - (2a² - 3ab) - (26-3a²) + ( -ab - 6) =

DAJE 70 PKT POTRZEBUJE NA TERAZ!!​


Odpowiedź :

Odpowiedź:

a) (2+-3)-(5-(-3))+(2-4)= -1-8-2= -11

b) -(2•4-3(-6))-(26-3•4)+(-6-6)=-(8-9)-(26-12)+(-12)= 1-14-12= -25

Odpowiedź:

[tex]a)\ \ (a+b)-(5-b)+(a-4)=a+b-5+b+a-4=2a+2b-9=\\\\=2*2+2*(-3)-9=4-6-9=4-15=-11\\\\\\b)\ \ -(2a^2-3ab)-(26-3a^2)+(-ab-6)=-2a^2+3ab-26+3a^2-ab-6=\\\\=a^2+2ab-32=2^2+2*2*(-3)-32=4-12-32=4-44=-40[/tex]